The Effect of Learning Model and Critical Thinking on Entrepreneurship Learning Outcomes of 11th Grade Student in 7 Vocational School Academic Year 2019/2020 - Nurul Shadrina Bintang; Dede Ruslan; M. Nasir (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
This study aims to determine the effect of learning models and critical thinking skills on student entrepreneurial learning outcomes. This study is an experimental study with a population of 83 students in 11th OTKP 7 Vocational School Medan. Research samples from OTKP 10Th grade were 41 students and from OTKP 2 class were 42 students and selected by total sampling technique divided into 2 groups that were taught with the Problem Based Learning model and the Inquiry Learning model. The research method uses quasi-experimental (Quasi Experiment) with 2 x 2 factorial design. The technique analysis data used is two-way ANAVA at a significant level = 0.05. after normality and homogeneity were tested, continued with Scheffe further tests. Hypothesis testing results obtained (1) there is a difference in the average value of entrepreneurship between students who are taught with the Problem Based Learning model (77.68) with students who are taught with Inquiry learning models (72.87) with Fcount (7.53)> Ftable (3,96), (2) there are differences in the average value of entrepreneurial learning outcomes of students who have high critical thinking skills (79.35) higher than the average value of entrepreneurial learning outcomes that have low critical thinking abilities (71.66 ) with Fcount (17.16)> Ftable (3.96).